2016
DOI: 10.1021/acs.nanolett.6b00348
|View full text |Cite
|
Sign up to set email alerts
|

Surface Area of Carbon Nanoparticles: A Dose Metric for a More Realistic Ecotoxicological Assessment

Abstract: Engineered nanoparticles such as graphenes, nanodiamonds, and carbon nanotubes correspond to different allotropes of carbon and are among the best candidates for applications in fast-growing nanotechnology. It is thus likely that they may get into the environment at each step of their life cycle: production, use, and disposal. The aquatic compartment concentrates pollutants and is expected to be especially impacted. The toxicity of a compound is conventionally evaluated using mass concentration as a quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 24 publications
4
39
0
Order By: Relevance
“…FLG could be found in the environment at several steps of its life cycle and especially in aquatic ecosystems where most pollutants can be concentrated. The size of nanoparticles implies a great specific surface area, which plays an important role in the impact on organisms [12,13]. Although many studies on the toxicology of nanoparticles have been carried out in vivo to date on model organisms such as rat but also in vitro on human cells [14,15], studies aimed to investigate the effect of graphene in the Environment are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…FLG could be found in the environment at several steps of its life cycle and especially in aquatic ecosystems where most pollutants can be concentrated. The size of nanoparticles implies a great specific surface area, which plays an important role in the impact on organisms [12,13]. Although many studies on the toxicology of nanoparticles have been carried out in vivo to date on model organisms such as rat but also in vitro on human cells [14,15], studies aimed to investigate the effect of graphene in the Environment are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its excellent interaction properties, graphene offers several opportunities and innovative solutions in various applications, such as contaminant removal and drug delivery 57 . However, graphene nanomaterials could be released into aquatic environments during the manufacture, use, and disposal of graphene-enabled products 8, 9 . During its life cycle, graphene may enter the gastrointestinal tract of livestock through food or drink consumption.…”
Section: Introductionmentioning
confidence: 99%
“…There was a lack of studies on the effects of graphene and reduced graphene oxide on ciliates, as well as characterization of graphene oxide NMs used in studies with ciliates. Standardized test protocols according to the International Organization for Standardization (ISO), the Organisation for Economic Co‐operation and Development (OECD), and the US Environmental Protection Agency (USEPA) were used in one study with bacteria , 2 studies with algae , 4 with freshwater invertebrates , 2 with a freshwater vertebrate‐fish , and 2 with an amphibian (Mottier et al was not included in the SSD analysis). Descriptions of experimental methodologies (other than USEPA, OECD, or ISO) were available in all publications.…”
Section: Resultsmentioning
confidence: 99%
“…In comparisons related to size (quality criteria), the surface area of synthetized GNMs was either measured in small number of studies or was reported as the theoretical value (∼2630 m 2 /g, ). The surface charge as a measure of stability of GNMs in water suspension was determined in some of the studies (Supplemental Data, Table S5).…”
Section: Resultsmentioning
confidence: 99%